Financial Education of Children and Youth - Nikola Fabris; Radoica Luburić (Journal of Central Banking Theory and Practice, 2016)
More and more individuals are becoming overindebted and facing difficulties in managing personal finance. On the other hand, financial products are becoming more and more complex, with numerous concealed risks. The level of financial literacy of youth and children is unsatisfactory both in the region and globally. Such a situation could lead to personal problems (financial distress), aggravated financial stability, with reverse adverse implications on economic growth. Many international studies have also confirmed these hypotheses. The aim of this paper is to point to the importance of financial education of youth and children, as well as to give some guidance on how to develop a national programme for increasing financial literacy. The paper develops a five-step programme with the main topics covering the drafting of a national strategy for developing financial literacy of youth and children and its implementation.
Keywords: I22; I25; 330; Financial Education; Children; Youth; Programme; National Strategy.